Experimental determination of aerosol particle sizes using supercontinuum radiation and estimation of the directional pattern of radiation from the filamentation region of femtosecond pulses - Babushkin, P. A.; Matvienko, Gennadij G.; Oshlakov, Viktor K.; Sukhanov, A. Ya (Radiophysics and quantum electronics)
According to the results of studying the interaction of high-power femtosecond pulsed radiation from a titanium-sapphire laser with the aerosol particles of an aqueous solution of NaCl, we estimate the directional pattern of Na emission from the filamentation region. It has been found that this directional pattern is characterized by minima in angular directions of 0 degrees and 180 degrees and a maximum in an angular direction between 20 degrees and 160 degrees. Based on the results of recording of supercontinuum radiation formed in the air and scattered by aerosol particles, the features of the aerosol particle size distribution have been determined. Gradient optimization methods using graphic processors were employed to speed up calculations. The neural network was used as an optimization method.